MyTEMP: Statistical Analysis Plan of a Registry-Based, Cluster-Randomized Clinical Trial. (August 2021) - Dixon, Stephanie N.; Sontrop, Jessica M.; Al-Jaishi, Ahmed; Killin, Lauren; McIntyre, Christopher W.; Anderson, Sierra; Bagga, Amit; Benjamin, Derek; Blake, Peter; Devereaux, P. J.; Iliescu, Eduard; Jain, Arsh; et al.
Background: Major Outcomes with Personalized Dialysate TEMPerature (MyTEMP) is a 4-year cluster-randomized clinical trial comparing the effect of using a personalized, temperature-reduced dialysate protocol versus a dialysate temperature of 36.5°C on cardiovascular-related death and hospitalization. Randomization was performed at the level of the dialysis center ("the cluster"). Objective: The objective is to outline the statistical analysis plan for the MyTEMP trial. Design: MyTEMP is a pragmatic, 2-arm, parallel-group, registry-based, open-label, cluster-randomized trial. Setting: A total of 84 dialysis centers in Ontario, Canada. Patients: Approximately 13 500 patients will have received in-center hemodialysis at the 84 participating dialysis centers during the trial period (April 3, 2017, to March 1, 2021, with a maximum follow-up to March 31, 2021). Methods: Patient identification, baseline characteristics, and study outcomes will be obtained primarily through Ontario administrative health care databases held at ICES. Covariate-constrained randomization was used to allocate the 84 dialysis centers (1:1) to the intervention group or the control group. Centers in the intervention group used a personalized, temperature-reduced dialysate protocol, and centers in the control group used a fixed dialysate temperature of 36.5°C. Outcomes: The primary outcome is a composite of cardiovascular-related death or major cardiovascular-related hospitalization (defined as a hospital admission with myocardial infarction, congestive heart failure, or ischemic stroke) recorded in administrative health care databases. The key secondary outcome is the mean drop in intradialytic systolic blood pressure, defined as the patients' predialysis systolic blood pressure minus their nadir systolic blood pressure during the dialysis treatment. Anonymized data on patients' predialysis and intradialytic systolic blood pressure were collected at monthly intervals from each dialysis center. Analysis plan: The primary analysis will follow an intent-to-treat approach. The primary outcome will be analyzed at the patient level as the hazard ratio of time-to-first event, estimated from a subdistribution hazards model. Within-center correlation will be accounted for using a robust sandwich estimator. In the primary analysis, patients' observation time will end if they experience the primary outcome, emigrate from Ontario, or die of a noncardiovascular cause (which will be treated as a competing risk event). The between-group difference in the mean drop in intradialytic systolic blood pressure obtained during the dialysis sessions throughout the trial period will be analyzed at the center level using an unadjusted random-effects linear mixed model. Trial status: The MyTEMP trial period is April 3, 2017, to March 31, 2021. We expect to analyze and report results by 2023 once the updated data are available at ICES. Trial registration: MyTEMP is registered with the US National Institutes of Health at clincaltrials.gov (NCT02628366). Statistical analytic plan: Version 1.1 June 15, 2021.